Efficacy and safety of etoricoxib in the treatment of osteoarthritis. Issue 3 (May 2008) - Sebba, Anthony
Osteoarthritis is a progressive disease that affects millions of people worldwide, but for which there are no curative options and indeed a limited number of medical treatment options. The American College of Rheumatology recommendations suggest administering either a traditional NSAID or a COX-2-selective inhibitor for pain relief. Traditional NSAIDs, such as naproxen, may have a higher risk of gastrointestinal (GI) events, while COX-2-selective inhibitors may have a higher risk of thrombotic cardiovascular (CV) events (with traditional NSAIDs and COX-2-selective agents appearing to have a similar CV risk). Etoricoxib, introduced in 2002, has been approved in over 60 countries worldwide for osteoarthritis. Large-scale studies addressing the efficacy, GI tolerability and potential for CV events with etoricoxib have now been published. Several patient types appear to benefit from etoricoxib, including those with CV risk factors and those requiring gastroprotective agents. In patients with CV risk factors, the benefits and risks of all NSAIDs should be weighed carefully in each patient, balancing the potential risks of treatment against the potential relief for pain and disability.